2006
DOI: 10.1002/chin.200611255
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Fate and Transport of Perfluorocarboxylates

Abstract: The supporting information provides additional details describing the basis and computations for the direct and indirect source emissions as well as environmental inventories and sinks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
146
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(156 citation statements)
references
References 1 publication
8
146
0
2
Order By: Relevance
“…Some studies suggested that PFOS and PFOA will reside in the aquatic compartment, to a greater extent than in the atmospheric medium (36). Gradual decreasing trends of PFCs in water and soils with the distance from the plant implied that the area directly influenced by the release of PFCs due to manufacturing are relatively small (<2 km in this work).…”
Section: Figure 1 the Concentrations Of Pfcs In Soil Surrounding Thementioning
confidence: 65%
“…Some studies suggested that PFOS and PFOA will reside in the aquatic compartment, to a greater extent than in the atmospheric medium (36). Gradual decreasing trends of PFCs in water and soils with the distance from the plant implied that the area directly influenced by the release of PFCs due to manufacturing are relatively small (<2 km in this work).…”
Section: Figure 1 the Concentrations Of Pfcs In Soil Surrounding Thementioning
confidence: 65%
“…FTOs are formed as a byproduct during FTOHs synthesis, and FTOHs are used as precursors to produce FTAs for fluorotelomer-based polymers. 9 NMeFOSE had a significant (r = 0.74, p < 0.01) correlation with NEtFOSE, and both were also significantly correlated with 8:2 FTO, 8:2 FTA, 8:2 FTOH, 10:2 FTOH, and 12:2 FTOH, suggesting that those compounds came from the same source regions. The two short-chain PFCs, 4:2 FTOH and NMeFBSA, were significantly (r = 0.49, p < 0.01) correlated with each other, suggesting these compounds are related to new products.…”
Section: Articlementioning
confidence: 89%
“…This trend is not surprising, given that the source of these compounds appears to be directly related to human population density. 9 Higher concentrations of 6:2 FTOH were measured at Guiyang (C8) and Taiyuan (C14), the cities with the largest coal and mine industries in China. Their use in lubricants in the mining machinery may be a factor here.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations